2021
DOI: 10.2174/1389202921999201130112116
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of bZIP Transcription Factors in Abscisic Acid Signaling and Drought Responses

Abstract: : Under drought stress, plants have developed various mechanisms to survive in the reduced water supply, of which the regulation of stress-related gene expression is responsible for several transcription factors. The basic leucine zippers (bZIPs) are one of the largest and most diverse transcription factor families in plants. Among the 10 Arabidopsis bZIP groups, group A bZIP transcription factors function as a positive or negative regulator in ABA signal transduction and drought stress response. These bZIP tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 115 publications
(156 reference statements)
1
15
0
Order By: Relevance
“…This was consistent with results of studies of polar [7] and Malus halliana [45]. Both gene Several studies have demonstrated the roles of plant bZIP proteins in numerous developmental processes and in responses to biotic and abiotic stresses [8,[49][50][51][52]. However, little is known about their functions in C. paliurus.…”
Section: Discussionsupporting
confidence: 88%
“…This was consistent with results of studies of polar [7] and Malus halliana [45]. Both gene Several studies have demonstrated the roles of plant bZIP proteins in numerous developmental processes and in responses to biotic and abiotic stresses [8,[49][50][51][52]. However, little is known about their functions in C. paliurus.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous transcription factors, including HD‐ZIP and bZIP, have been found to undergo post‐translational modification during the responses of plants to hormones and environmental stimuli (Himmelbach et al ., 2002; Hill, 2015; Skelly et al ., 2016; Joo et al ., 2021). In our previous study, we demonstrated that CaDRHB1, a member of the HD‐ZIP I subfamily, functions as a positive modulator for drought tolerance via ABA‐mediated stomatal closure (Lim et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Among the differentially expressed TF-coding genes, TF families with known functions were represented; however, the exact functions of most of these genes remain unknown. The role of some members of TF families, such as ARF, bZIP, MYB-related, and WRKY, which exhibited differential regulation among potato cultivars, are well known in root responses to drought stress ( Jiang et al., 2017 ; Joo et al., 2021 ; Wei et al., 2021 ; Yang et al., 2021 ). Differential regulation of the same gene family members in different potato cultivars may result in different regulatory networks that can determine cultivar-specific rooting depth and root response to drought stress.…”
Section: Discussionmentioning
confidence: 99%